Bugallo, Lucila and Mario Vilca (comps.) (2016). Wak'as, devils and the dead. Signigicant otherness in the Andean worlds. San Salvador de Jujuy: National University of Jujuy-EDIUNJU-IFEA - Muñoz Morán, Oscar (2017)
W’akas, devils and dead raises new readings to understand the presence in the Andes of a wide spectrum of entities and beings from the other world that interact with the local population. This review highlights its relevance, as well as the concept of "fluidity" that  most collaborators handle to characterize souls or supays, among others.